PROMOTING ACTIVE AND HEALTHY AGING THROUGH MULTI-PRONGED PUBLIC HEALTH STRATEGIES - Miguel Melo (PsychTech & Health Journal)
In this issue of the PsychTech & Health Journal, a set of articles is presented that mainly address problems that currently represent challenges for public health. Overall, the need for early identification of syndromes associated with significant loss of functionality and quality of life stands out. It is also relevant to know the determinants that guide actions to promote quality of life and highlight the advantages of active ageing. The works we publish add to the scientific evidence that can guide support and face the problems that now represent a challenge in Public Health.